Parenting style in a collectivist cultures of Malaysia. - Keshavarz, Somayeh; Baharudin, Rozumah (EuroJournals, 2009)
The article reviews empirical studies which emphasize that parenting styles are strongly influenced by the cultural context of the society. Cultural differences in values, described as individualism-collectivism, similarly shape understanding of the forms (e.g. authoritative, authoritarian, and permissive parenting styles) and interpretation of parenting styles. The review indicates that Malaysian parents from the three ethnic groups (i.e., Malay, Chinese and Indian) are similar with other parents from collectivist countries which endorse authoritarian parenting more than individualist parents, and do not regard it as an unfavorable style of parenting.